2017
DOI: 10.1080/0142159x.2016.1271944
|View full text |Cite
|
Sign up to set email alerts
|

Effective methods of teaching and learning in anatomy as a basic science: A BEME systematic review: BEME guide no. 44

Abstract: This review provides evidence in support of the use of alternatives to traditional teaching methods in anatomy, in particular, the use of CAI/CAL with a number of high quality, low risk of bias studies supporting this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
0
9

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(121 citation statements)
references
References 70 publications
5
107
0
9
Order By: Relevance
“…The evidence base for modern teaching tools is expanding: a systematic review on 29 articles concluded that computer‐assisted learning and instruction showed better results than traditional teaching interventions, being a valuable adjunct to dissection . Another meta‐analysis of 36 studies ( n = 2226) demonstrated that 3D visualization technologies yielded significantly higher test scores, spatial contextualization and user satisfaction compared with all other methods …”
Section: Traditional Teaching Versus the Multimodal Approach In Surgimentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence base for modern teaching tools is expanding: a systematic review on 29 articles concluded that computer‐assisted learning and instruction showed better results than traditional teaching interventions, being a valuable adjunct to dissection . Another meta‐analysis of 36 studies ( n = 2226) demonstrated that 3D visualization technologies yielded significantly higher test scores, spatial contextualization and user satisfaction compared with all other methods …”
Section: Traditional Teaching Versus the Multimodal Approach In Surgimentioning
confidence: 99%
“…The evidence base for modern teaching tools is expanding: a systematic review on 29 articles concluded that computer-assisted learning and instruction showed better results than traditional teaching interventions, being a valuable adjunct to dissection. 10 Another meta-analysis of 36 studies (n = 2226) demonstrated that 3D visualization technologies yielded significantly higher test scores, spatial contextualization and user satisfaction compared with all other methods. 25 This is certainly not to suggest that they are superior alternatives to cadaveric dissection, with equally significant evidence to the contrary, 28 although institutions have already been reported to act on this by phasing out dissection.…”
Section: D Printingmentioning
confidence: 99%
“…Knowledge retention, and the factors that influence retention, is important for anatomy education and thus have been of great interest to educators (Logan et al, 2011;Bergman et al, 2013;Drake et al, 2014;Jurjus et al, 2014;McBride and Drake, 2016). This is leading many educators to review their anatomy teaching methodologies, and the level to which it is integrated with clinical subjects within their program (Drake, 2007;Parmar and Rathinam, 2011;Malau-Aduli et al, 2013;McBride and Drake, 2016;Doomernik et al, 2017;Losco et al, 2017). However, the introduction of teaching innovations and integration of anatomy within medical curricula has not been uniform or simultaneous across different institutions (McBride and Drake, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…[15] Computer-assisted learning involves any teaching method that uses a digital platform as an SDL technique that includes both online and offline learning opportunities. [16] Although CAI is a broad term that includes both online and offline modalities, in newer terminology, specifically referring to online learning methods includes terms such as “web-based learning,” “web-based training,” and “e-learning.”[17181920] According to Alavi and Leidner, e-learning is the virtual learning field in which the interaction among the learner, teachers, and classmates and educational equipment are all different from the traditional method because in virtual environments electronic technology tools are used as an instrument for supporting and improving the learning process. [21]…”
Section: Introductionmentioning
confidence: 99%
“…Other educational features, such as practice and test fields (for example, online multiple-choice questions with quick feedback), can be provided by the digital platform. [162223] The advantages of multimedia education are flexible classroom time, increased student's autonomy, freedom to do more in-depth training, and less time for the course preparation. The high cost, the need for technical specialists in electronic media, and the lack of social interactions among learners are cited by the disadvantages of this method.…”
Section: Introductionmentioning
confidence: 99%